Correlation Between Walking Ability and Monthly Care Costs in Elderly Patients After Surgical Treatments for Hip Fractures - Koki Abe; Kazuhide Inage; Keishi Yamashita; Masaomi Yamashita; Akiyoshi Yamamaoka; Masaki Norimoto; Yoshinori Nakata; Takeshi Mitsuka; Kaoru Suseki; Sumihisa Orita; Kazuki Fujimoto; Yasuhiro Shiga; et al. (Annals of Rehabilitation Medicine, 2018)
Objective To validate the relationship between residual walking ability and monthly care cost as well as long-term care insurance (LTCI) certification level in elderly patients after surgical treatment for hip fractures in Japan. Methods Elderly patients aged >75 years who underwent surgical treatment for hip fractures in our hospital were included. The preand post-surgical (6-month) walking ability and LTCI certification and the presence or absence of dementia was determined from medical records and questionnaires. Walking ability was classified into 6 levels used in our daily medical practice. Based on these data, we correlated the relationship between walking ability and the LTCI certification level. Further, based on the official statistics pertaining to the average monthly costs per person at each LTCI certification level, we evaluated the relationship between walking ability and monthly care cost. Results A total of 105 cases (mean age, 80.2 years; 16 men; 39 patients with dementia) were included. The correlation between walking ability and average monthly cost per person as well as LTCI certification level at 6 months postoperatively (r=0.58) was demonstrated. The correlation was found in both groups with and without dementia. Conclusion The ability to walk reduced the cost of care in elderly patients who experienced hip fracture, regardless of the presence of dementia.